Can an ethical work climate influence payment discipline? - Tanja Salamon; Maja Mesko (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: All European companies are faced with the lack of payment discipline, which often affects even their survival. One of the key reasons for the lack of payment discipline is poor business ethics, which is primarily introduced with the subject of ethical climate in the literature. For this reason, we wanted to determine whether a company's ethical climate influences its payment discipline. Design/methodology/approach: In the research, we used Arnaud's measurement instrument (2010) that helped us to identify six dimensions of ethical climate. The data about a company's ethical climate were later compared with the data about its payment discipline, calculated using the Dun & Bradstreet rating agency methodology. We included in the sample 273 Slovenian companies, which represented 9.1% of all companies invited to take part in the survey (2978 Slovenian enterprises with 10 or more employees). Findings: We established that (among the six dimensions of the ethical climate) the dimension "moral sensitivity - the lack of norms of empathetic concern" had statistically significant influence on the average delay of payment, and the more significant for the company the lack of norms of empathetic concern was, the longer the delay of the payment to suppliers would be. Our conclusion is that the appropriate forms of the incorporation of training and education on ethical subjects into business studies may increase the payment discipline of companies. Originality/value: The present study represents an important contribution to understanding the causes of payment defaults. The study also includes non-financial antecedents of payment discipline, which represents a new, important contribution of the research.
Keywords: 650; ethical climate; ethical work climate; late payments; payment discipline